Towards integrated control of varroa: 4) varroa mortality from treating broodless winter colonies twice with oxalic acid via sublimation. Issue 3 (27th May 2018) - Al Toufailia, Hasan; Scandian, Luciano; Shackleton, Kyle; Ratnieks, Francis L. W.
Abstract : In winter 2014–2015, we treated 22 broodless honey bee colonies with 2.25 g oxalic acid (OA) via sublimation on 23 December 2014 and again on 6 January 2015. Varroa numbers were determined before and after OA application by extracting mites from samples of workers. Mean varroa mortality from both applications combined was 99.6%, which is greater than the 97.6% mortality from a single treatment shown by our previous research. We determined whether double OA application was more harmful than single application, by comparing 12 colonies that had been double treated with 12 single-treated colonies. There was no difference in colony performance on 5 May 2015 (100% survival in both groups; 5.5 frames of brood in single-treated colonies vs. 5.3 in double-treated colonies). Varroa mortality from the first application, 96.8%, was significantly higher, p  < 0.001, than from the second 87.2%. Ten of the 22 study colonies were killed 14 days after the second OA application to precisely quantify varroa levels. The mean number surviving was 6 (range 2–18). Worker numbers averaged 5, 644 bees (range 3, 352–8, 692). To confirm the results a small second trial was made the following winter with 10 colonies. Results were similar. Again, combined varroa mortality was very high, 99.4%, with greater mortality from the first, 98.3%, than the second, 64.1%, application. Overall, the results indicate that double application of OA is worthwhile to beekeepers in varroa management. It is not harmful to colonies and by killing c. 99.5% of the varroa it reduces varroa populations to such an extent that 7–8 doublings, which would take more than one year, are needed to build back to the original level.